Evolución de la remuneración básica unificada y su incidencia sobre el empleo, cantón La Maná, periodo 2013 – 2015 - Oto Calero, Evelyn Abigail (2016)
This research investigates the remuneration and its effect on the labor market of La Maná Canton, mainly considering the economic activity of the various productive sectors in th e context of small and medium enterprises (PYMES). The canton maintains its productive matrix restricted due to the low performance of local authorities, resulting low value added production is obtained; business culture of the area is negligible. There is some agreement of the economically active population (EAP) in their socio - economic situation, they assume that the general level of wages is based on the needs of household consumption. The results of the surveys of urban and rural population; as well as interviews with several production and trading companies, they have been the source of real and tangible information on the subject in question. The compensation is determined in correspondence to the Unified Salary (SBU); Ecuadorian law also determines the Living Wage General (SMVG) and Sectoral Minimum Wage (SMS ) . The latter are unknown to the in habitants. . Not investigation concerning the issue in question in La Maná, so the project serves as a reference for future research, all variants concentrated in the labor market of the territory is exposed.